URGENSI KEBIJAKAN REKLAMASI PANTAI UTARA DKI JAKARTA DAN DAMPAK YANG DITIMBULKAN - Insan Harapan Harahap; Nana Suryana (TATALOKA, 2019)
Controversy related to the reclamation policy of the DKI Jakarta’s North Coast is endless. Its reclamation policy is reputed inappropriate with the prevail procedure, its policy becomes a fighting zone between authority and entrepreneur, beside them bribe cases and corruption was shown covering its reclamation policy of DKI Jakarta’s North Coast. Therefore, writer tried to explain whose the actor belongs to its reclamation project. This research will be descriptive, which the data and information’s used in this research contains of documentation studies and interview with the related institution whose has relation with the reclamation project of DKI Jakarta’s North Coast. The result of this research will be concluded that the reclamation project of DKI Jakarta’s North Coast has a positive and negative impact. This reclamation project can not only solve the existing problems, instead of creating new problems associated with adverse environmental impacts. In addition, the reclamation project disrupted the livelihood of fishermen in the North Coastal area of DKI Jakarta.